Penerapan Metode Topsis Untuk Rekomendasi Penetapan Siswa Berprestasi Penerima Penghargaan Tahunan Di Tingkat Sekolah Menengah Pertama - Cindy Shentia; Lis Utari (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
In a school, the ranking of outstanding students is usually only chosen based on their report card scores, as well as in SMP PGRI 16. The selection of outstanding students at SMP PGRI 16 is only based on grades (raport) which are ranked 1 to 3 only. In the selection process there are many opportunities to make wrong decisions because the student selection process is only based on one aspect, namely student scores (raport), while the values of attitudes and achievements obtained outside of school are not taken into consideration as additional criteria for determining students who are considered outstanding and receive annual awards. This means that most likely the selected outstanding students do not reach the desired standard and do not get the best candidates. The purpose of this research is as an alternative way for schools to determine outstanding students so that they are not based solely on academic scores, and there is no cheating in the selection of outstanding students. The method used in this study is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The results of this study are that the TOPSIS method can provide the best results from the criteria and weights that have been determined. From the calculation results with the TOPSIS method, it was obtained by a student named MRF with a preference value of 0.9742